The executive and the elephant : a leader's guide for building inner excellence - Daft, Richard L. (San Francisco, CA : Jossey-Bass, 2010)
"Lessons for leaders on resolving the ongoing struggle between instinct and the creative mindKings, heads of government, and corporate executives lead thousands of people and manage endless resources, but may not have mastery over themselves. Often leaders know that right action is important, but have little (if any) understanding of what prevents them from acting in accordance with their intentions. In this important book, leadership expert Richard Daft portrays this dilemma as a struggle between instinct (elephant) and intention (the executive) using the most current research on the intentional vs. the habitual mind to explain how this phenomenon occurs. Based on current research and real-life examplesOffers leaders a method for directing themselves more productivelyWritten by an expert in leadership, organizational performance, and change managementThrough real-life examples and recent studies in psychology, management and Eastern spirituality Daft provides guidance to all of us who struggle finding our own balance and cultivating the behavior of others"--
Machine generated contents note: Preface. -- Acknowledgments. -- Part One The Two Selves. -- 1. The Problem of Managing Yourself. -- The Conflict Between Knowing and Doing. -- The Universal Failure of Willpower. -- The Divided Self: Executive and Elephant. -- Learning to Lead from Your Inner Executive. -- Purpose of This Book. -- 2. Recognize Your Two Selves. -- Levels of Consciousness. -- Two Voices Within. -- Why Your Mind Is Filled with Automatic Thoughts. -- Unfocused Elephant Mind Versus Focused Executive Presence. -- Small Box Versus Large Mind. -- Part Two Ways You May Mislead or Delude Yourself. -- 3. Three Tendencies That Distort Your Reality. -- Your Internal Judge. -- Your Internal Magician. -- Your Internal Attorney. -- 4. Every Leader's Six Mental Mistakes. -- Reacting Too Quickly. -- Inflexible Thinking. -- Wanting Control. -- Emotional Avoidance and Attraction. -- Exaggerating the Future. -- Chasing the Wrong Gratifications. -- Part Three How to Start Leading Yourself. -- 5. Engage Your Intention. -- Visualize Your Intention. -- Verbalize Your Intention. -- 6. Follow Through on Your Intentions. -- Write Down Your Intentions. -- Set Deadlines. -- Design Tangible Mechanisms. -- 7. Calm Down to Speed Up. -- Get Connected. -- Let It Happen. -- Sit by Your Problem. -- Relax Your Body. -- Calm Your Elephant by Acting the Part or Making a Gentle Request. -- 8. Slow Down to Stop Your Reactions. -- Stop and Think. -- Stop Interrupting. -- Detach from your Emotions and Impulses. -- Just Say No. -- Employ Punishment. -- Part Four Become Aware of Your Inner Resources. -- 9. Get to Know Your Inner Elephant. -- Know Yourself. -- Solicit Feedback. -- Take Advantage of a Setback. -- 10. Expand Your Awareness. -- Review the Day. -- Contemplate Creatively. -- Part Five Reach for the Heights. -- 11. Sharpen Your Concentration. -- Focus Your Attention. -- Focus on Means, Not Ends. -- Slow Down, Look, and Listen. -- Focus on People. -- 12. Develop Your Witness. -- Turn Inward to Develop Your Witness. -- Use Radical Self-Inquiry. -- Who Am I? -- 13. Reprogram Yourself. -- Repeat a Mantra. -- Prayer May Help, but Not the Way You Think. -- 14. Mend Your Mind with Meditation. -- Why Meditate? -- An Easy Way to Start. -- Two Essentials. -- Mindfulness Meditation. -- Try Visual Rather Than Verbal. -- Contemplative Meditation. -- Part Six Can You Lead from a People Frame of Reference? -- 15. Change Your Frame to See People. -- What Is Your Frame? -- From Leading Objects to Leading Humans. -- How to Change Your Frame. -- 16. Change Your Frame to Ask Questions. -- From Answering Questions to Asking Questions. -- In All Things, Consult. -- 17. Living and Leading from Your Inner Executive. -- Higher Consciousness Revisited. -- When Her Mind Went Quiet. -- Answers to Individual Questions. -- Final Thoughts. -- The Author. -- Index.
Includes bibliographical references and indexes.
Keywords: Leadership